Business Feasibility Study On Hotel Operates Inside University Campus - Bujang, Nazarudin; Muslim, Aini Khalida; Omar, Siti Sarah; Dasril, Yosza (Research in Management of Technology and Business, 2020)
The business feasibility study focused on the proposed development of a hotel project inside university campus. The market study provided a demographic assessment, forecast demand evaluation, financial performance projection and economic assessment review of the subject area to determine the overall business feasibility of a new hotel operates and run inside university campus. The main objective of the study is to develop market understanding and to propose the hotel concept and capacity to University Holdings management team. The market feasibility study addressed the estimated operating performance of the hotel project. It also provides recommendations to the size, capacity and scope of the hotel development. Hotel occupancy rate, average daily room rate and sales revenue projections of the hotel were determined and calculated based on the detailed review of comparable sales, field research data and surveys done on potential customers. The research methodology used a mixed-method design. Quantitative method used on collecting and analyzing data from targeted customers such as university staff, students, parents, guests of selected hotels and government employees within close proximity of the campus. In addition, qualitative method used during benchmarking visit to eight local public universities, which already have hotels operate inside the campuses. The outcome of the research was an extensive business feasibility report for the hotel based on the numerical evidence gathered and conclusions drawn from the interview sessions with key stakeholders.